Potensi Ekonomi Tanaman Hias Penyerap Karbon Berkemasan Kokedama di Kota Semarang - Fatima, Nurul; Haris, Amnan (Business and Accounting Education Journal, 2024)
This research aim to examine the economic potential of the ornamental kokedama plant as a carbon sink in the context of environmental management and green economic development. Kokedama, a traditional Japanese technique of growing plants using coconut fiber, has attracted interest as a decorative element and an effective carbon sink. This research uses a qualitative descriptive method with a case study approach on kokedama business actors in Semarang City. Data was collected through interviews, observation and BEP analysis. The research results show that kokedama has significant economic potential, especially in environmentally conscious urban markets. The break-even value (BEP value) of ornamental kokedama plants is achieved at a value of IDR 6,646,710. The amount of production that must be sold to break even is 232 pcs. This research concludes that the development of ornamental kokedama plants as carbon sinks not only offers economic benefits for business actors, but also makes a positive contribution to climate change mitigation efforts.